(untitled) (Experimental biology, 2018)
The study was conducted to study the frequency distribution of alleles and genotypes of polymorphic variants of folate cycle genes methionine synthase (MTR) A2756G, rs1805087; methionine synthase reductase (MTRR) A66G, rs1801394; and 5,10-methylenetetrahydrofolate reductase (MTHFR) C677T, rs1801133in women of the Kazakh ethnic group with pregnancy complications. The research was conducted using the "case-control study". The test group was consisted by 121 pregnant women who had in anamnesis complications in the first two or more pregnancies, including miscarriages. The control group was consisted by 120 pregnant women who had two or more normal outcomes of the first two pregnancies without pregnancy complications in anamnesis. The material of the study was genomic DNA isolated from the venous blood of the examined women. The definition of genetic polymorphisms was carried out on the RealTime CFX96 amplifiers (BioRad, USA). Statistical analysis in the online-program SNPstats using the codominant, dominant, recessive, overdominant and log-additive inheritance models revealed no statistically significant differences in the frequencies of the observed polymorphisms in the women of the test and control groups. The obtained results of the studies indicate supplementing information on the prevalence of the polymorphic alleles of the folate cycle genes MTR, MTRR, MTHFR among women of the Kazakh ethnic group. However, further molecular epidemiological studies are needed to unambiguously interpret the contribution of environmental and genetic factors to the course of pregnancy.